A Review on Genesis, Growth and Development of Bengal Artisanal Silk Industry in India - Chandan Roy (Integrated Journal for Research in Arts and Humanities, 2022)
This paper explores how the silk production in India started flourishing from mid of the seventeenth century when the demand for cheaper Bengal silk began to rise in European market. Initially Dutch merchants were collecting the silk from domestic market for exporting it to Europe and later English East India Company (EEIC) took over the control of silk trade spreading their tentacles in different parts of Bengal. In order to improve the quality, EEIC introduced Italian technology of reeling in Bengal in 1769, though Bengal sericulture was unable to adapt the technology. Bengal economy was going through several natural calamities and domestic disturbances. From 1813 the company started selling its filatures. The economic power of dadani merchant, money-lenders started growing from this period and they formed a new middle class while the situation of artisan and farmer classes deteriorated. The condition of native artisans of Bengal further worsened under the rule of British Monarch as the Industrial Revolution in West set in. Being potential competitor of Machester Silk, Bengal silk faced serious crisis and eventually Bengal silk industries were transformed into suppliers of raw materials, which was driven by the national interest interests of the British Monarch.